2018
DOI: 10.4103/ijdr.ijdr_97_15
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of matrix metalloproteinase-8 in gingival crevicular fluid and periodontal diseases

Abstract: The findings of this study can be used by practitioners of dentistry to establish a proper diagnosis and appropriate treatment of periodontal disease by measuring the scale of MMP-8, to prevent or to minimize further complication in periodontitis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…[24][25][26] Several types of inflammatory and redox/oxidative stress biomarkers associated with both systemic diseases and oral diseases have been detected in saliva and GCF, such as IL-1 , IL-6, IL-8, tumor necrosis factor-, matrix metalloproteinase-8 (MMP-8), and reduced glutathione GSH levels. 27,28 E-cigs are battery-operated devices that deliver nicotine, flavorings, and other constituents by heating e-liquid. The composition of e-liquids varies greatly due to the broad range of nicotine concentrations and flavoring chemicals, thus resulting in different aerosol mixtures inhaled by EC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] Several types of inflammatory and redox/oxidative stress biomarkers associated with both systemic diseases and oral diseases have been detected in saliva and GCF, such as IL-1 , IL-6, IL-8, tumor necrosis factor-, matrix metalloproteinase-8 (MMP-8), and reduced glutathione GSH levels. 27,28 E-cigs are battery-operated devices that deliver nicotine, flavorings, and other constituents by heating e-liquid. The composition of e-liquids varies greatly due to the broad range of nicotine concentrations and flavoring chemicals, thus resulting in different aerosol mixtures inhaled by EC.…”
Section: Discussionmentioning
confidence: 99%
“…Several types of inflammatory and redox/oxidative stress biomarkers associated with both systemic diseases and oral diseases have been detected in saliva and GCF, such as IL‐1β, IL‐6, IL‐8, tumor necrosis factor‐α, matrix metalloproteinase‐8 (MMP‐8), and reduced glutathione GSH levels 27,28 …”
Section: Discussionmentioning
confidence: 99%
“…But we did observe a tendency toward higher MMP-8 levels in patients with periodontitis compared to levels in patients with gingivitis. Other studies also found higher levels of MMP-8 in the saliva and gingival crevicular fluid of patients with periodontitis [28,[39][40][41]. The increased levels of MMP-8 may be associated with inflammation around teeth and implants and serve as a useful adjunctive diagnostic tool in periodontal and periimplant diseases [42,43].…”
Section: Discussionmentioning
confidence: 88%
“…Prescribing zinc complement has both treatmental and preventive effects in periodontitis patients. 15…”
Section: Discussionmentioning
confidence: 99%